PFK2/FBPase-2 is a potential target for metabolic engineering in the filamentous fungus Myceliophthora thermophila - Hu, Die; Zhang, Yongli; Liu, Defei; Wang, Depei; Tian, Chaoguang (Frontiers in Microbiology, 2022)
The key enzyme 6-phosphofructo-2-kinase (PFK2)/fructose-2,6-bisphosphatase (FBPase-2) is responsible for regulating the rates of glycolysis and gluconeogenesis in eukaryotes. However, its functions and mechanisms in filamentous fungi remain largely enigmatic. In this study, we systematically investigated the function of this enzyme in Myceliophthora thermophila, a thermophilic filamentous fungus with great capacity to produce industrial enzymes and organic acids. Our results showed that the M. thermophila genome encodes three isomers, all with the PFK2/FBPase-2 structure: pfk2-a, pfk2-b and pfk2-c. Overexpression of each gene revealed that endogenous expression of pfk2-c (PFK2 activity) promoted glucose metabolism, while overexpression of pfk2-a (FBPase-2 activity) inhibited strain growth. Using knockouts, we found that each gene was individually non-essential, but the triple knockout led to significantly slower growth compared with the wild-type strain. Only the pfk2-a single knockout exhibited 22.15% faster sugar metabolism, exerted through activation of 6-phosphofructo-1-kinase (PFK1), thereby significantly promoting glycolysis and the tricarboxylic acid cycle. The FBPase-2 deletion mutant strain also exhibited overflow metabolism, and knocking out pfk2-a was proved to be able to improve the production and synthesis rate of various metabolites, such as glycerol and malate. This is the first study to systematically investigate the function of PFK2/FBPase-2 in a thermophilic fungus, providing an effective target for metabolic engineering in filamentous fungi.